Exploring the Antecedents and Outcomes of Entrepreneurial Well-Being: Empirical Evidence From Iranian Rural Entrepreneurs - Karimi, Saeid; Reisi, Sima (Frontiers in Psychology, 2022)
Studies regarding rural entrepreneurs in developing countries and, specifically, their well-being have not been sufficiently developed in the literature. The present study was an attempt to fill this gap and to examine important antecedents and outcomes associated with entrepreneurial well-being among a sample of 102 Iranian rural entrepreneurs. This research established a theoretical research model that highlighted the relationships among job fit, entrepreneurial passion, well-being, and persistence. The results of structural equation modeling supported the hypothesized model. In particular, the results indicated that higher job fit was associated with higher levels of entrepreneurial well-being through an entrepreneurial passion mechanism. Moreover, the results supported the hypothesized serial mediating effect. In other words, a high level of job fit enhances entrepreneurial persistence through a high level of entrepreneurial passion and well-being. This study provides significant input to policymakers and practitioners in their efforts to promote the antecedents and outcomes of well-being among rural entrepreneurs.